Heat Transfer between Immersed Surfaces and Gas-Fluidized Beds - Saxena S.C. (My University, 2025)
This chapter discusses the available experimental and theoretical information concerning the bed to surface heat-transfer coefficient. The high heat transfer rates achieved for boiler tubes immersed in fluidized-bed coal combustors, along with their in situ capability to remove SOx and suppress the emission of NOx in high-pressure systems, have led to their exploitation as a promising technology for the generation of electrical power from sulfur-rich coal. The atmospheric fluidized-bed combustion (AFBC) technology has been claimed to be ready for commercialization for some time. On the other hand, thermodynamic analysis has shown that pressurized fluidized-bed combustion (PFBC) of coal in the combined-cycle mode is very efficient and economically preferable. Heat transfer rate from an immersed surface in a gas-fluidized bed depends upon a number of factors, such as the size, size range, shape, and properties of the bed particles; operating conditions, temperature, pressure, fluidizing velocity, and properties of the gas; shape, size, surface finish, and orientation of the heat transfer surface; the relative size of the heat transfer surface and the fluidized bed; and on the design of the gas distributor plate. © 1989 Academic Press Inc.